2006
DOI: 10.1002/j.0022-0337.2006.70.4.tb04091.x
|View full text |Cite
|
Sign up to set email alerts
|

North American Dental Students’ Perspectives About Their Clinical Education

Abstract: Many North American dental schools face the challenge of replacing the majority of their "boomer generation" clinical instructors over the next ten years as this cohort of faculty reaches retirement age. Developing a new cadre of clinical instructors poses a substantial faculty development challenge: what instructional techniques should be integrated into routine educational practice by the dental faculty of the future, and what aspects of the clinical learning environment should be addressed to improve the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
124
1
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(149 citation statements)
references
References 36 publications
11
124
1
6
Order By: Relevance
“…It may also explain the apparent contradictions in student experiences of feedback. Students in this study were able to reflect on and articulate the expected behaviours and what they would need to hear from supervisors to support their learning in the clinical environment, and these were consistent with the literature .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…It may also explain the apparent contradictions in student experiences of feedback. Students in this study were able to reflect on and articulate the expected behaviours and what they would need to hear from supervisors to support their learning in the clinical environment, and these were consistent with the literature .…”
Section: Discussionsupporting
confidence: 74%
“…During patient treatment sessions, the clinical teacher occupies the multiple roles of a teacher, a clinical supervisor responsible for the safety of the patient, and of an expert clinician, and is expected to continuously switch between these roles. It has been documented that the behaviour and the approach of clinical teachers may enhance or detract from the learning experience of students .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the students' dominance on oral surgical procedures through their confidence levels. It should be considered that confidence level is a subjective measurement that cannot reflect the actual ability or skill of an individual . Stacey MA et al reported that undergraduates gained significantly higher scores regarding clinical competency from their assessments as compared to lecturers’ assessments .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the patient‐centred approach, what is best for patients becomes the central focus . Research shows that traditional approaches do not properly respond to the interplay of needs and interests of the stakeholders involved in CE . For instance, Dehghan et al found that whilst students valued the opportunity to provide more comprehensive care under the group practice system, they were concerned about not being exposed to the experiences of instructors and students outside of their group, which they recognised as an advantage of the student‐centred, discipline‐based system .…”
Section: Limitations Of Current Approachesmentioning
confidence: 99%